CHILD ABUSE REPRESENTED IN MATILDA BY DANNY DEVITO - Wongui, Maria Stevani; Winardi, Yohanes Kurniawan; Fadilah, Eka (Universitas Widya Kartika Surabaya, 2023)
This article aims to reveal the way abuse experienced by children characters in Matilda (1996) is represented. Using Qualitative-Interpretive method, this research analyzed the cinematic elements that helps accentuate details or information related to child abuse represented in the film and focuses only on the abuse experienced by the children characters. This research used Stuart Hall’s (1997) theory of Representation, Clark’s (2007) classification of Child Abuse, and Kuhn & Westwell’s (2020) theory of Film Style. The result of this research shows that mise-en-scene, shot, and angle, are the elements used in the film to represent child abuse. This research also reveals that the children characters in Matilda (1996) experienced neglect, physical abuse, and emotional abuse.